Music in diagnostics: using musical interactional settings for diagnosing autism in adults with intellectual developmental disabilities. Issue 4 (1st October 2016) - Bergmann, Thomas; Sappok, Tanja; Diefenbacher, Albert; Dziobek, Isabel
Abstract : Various approaches to the diagnosis of autism spectrum disorders (ASDs) in children use the non-verbal communicative quality of music. However, ASD is frequent but under-diagnosed in adults with intellectual developmental disabilities (IDDs), so valid diagnostic instruments are urgently needed. Against this background, the Music-based Scale for Autism Diagnosis (MUSAD) was developed. A course of 13 musical interactional situations associated with instruments and activities was created to elicit autism diagnostic relevant behaviours. Eighty-eight items were derived assessing social affect, inflexible behaviours and sensory–motor issues. The MUSAD was applied from January 2010 to December 2011 in n = 91 adults with IDD suspected of having ASD; feasibility was assessed in n = 80 (April 2010 to December 2011). Reasons for non-feasibility of the MUSAD and the Autism Diagnostic Observation Schedule (ADOS) were compared in n = 40. Interrater agreement was analysed for one case by 12 independent raters; plausibility was assessed using questionnaires. Feasibility in applying the MUSAD was 95% (76/80). More individuals with severe language impairments were testable with the MUSAD as compared to the ADOS. Interrater agreement was .67 (ICC single measure), while items and scoring showed good plausibility. The MUSAD appears to be a promising measure for diagnosing ASD in adults with IDD, especially in individuals with limited verbal abilities.